Achievement Motivation of University Students - Elias, Habibah; Abdul Rahman, Wan Rafaei (Universiti Putra Malaysia Press, 1995)
The achievement motivation of 1050 Universiti Kebangsaan Malaysia students was measured in relation to faculty and year of study, ethnic group, gender and place of origin. Three other dependent variables, locus of control, attitude towards learning and study habits, were also examined. The tests used were the thematic apperception test, Rotter's internal and external scale, the attitude scale and the study scale. The results showed that there were significant differences in achievement motivation among students based on faculty (F (5,939) = 13.39, P < .05), year of suldy (F (1,939 = 4.55, P < .05) and ethnic group (F (2,939) = 6.58, P < .05). On locus of control, it was found that male students were more internal than female students (F (1,876) = 7.22, P < .05). Significant differences were also found in attitudes of subjects in relation to ethnic group (F (2,828)= 9.93, P < .05), year of study (F (1,828) = 5.03, P < .05) and faculty (F (1,888) = 8.18, P < .05).